25-4x=-(x-26)

Simple and best practice solution for 25-4x=-(x-26) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25-4x=-(x-26) equation:



25-4x=-(x-26)
We move all terms to the left:
25-4x-(-(x-26))=0
We calculate terms in parentheses: -(-(x-26)), so:
-(x-26)
We get rid of parentheses
-x+26
We add all the numbers together, and all the variables
-1x+26
Back to the equation:
-(-1x+26)
We get rid of parentheses
-4x+1x-26+25=0
We add all the numbers together, and all the variables
-3x-1=0
We move all terms containing x to the left, all other terms to the right
-3x=1
x=1/-3
x=-1/3

See similar equations:

| 5=z/3+3 | | 1/3(6x+9)=5(2x-3) | | 5x+14=12+8x+2 | | -19c+20=-20c | | 39.16+0.50x=120 | | 67-u=212 | | 2x-100=6x+20 | | 10(-n)-1=29 | | -15-13s+1=18-11s | | 6n+4n-9n+5n=18 | | 10-x=1/3(3x-6) | | 120=39.16+0.50x | | 8d=4d+12 | | 6-18z=-5-19z | | 64=y/8 | | 9p-36=3p | | 15x-14+3x=10(x-1) | | 2h-12=-2h+4 | | u/3-3=5 | | 5x-40=-3 | | 5n+14=2n+20 | | 7=t/2+4 | | (x-1)+7=3 | | 3=1+2m | | 30-7x=550 | | 8y-5y+2y+2y+y=20 | | -2/3(18x-12)/4=5x-3-11 | | 3.1+10m=7.64 | | u/2+7=6 | | 5g+3g=8 | | x-20=153° | | x/4+x=x/2-3 |

Equations solver categories